Coupled Bilayer Photonic Crystal Slab Electro-Optic Spatial Light Modulators - Yi-Chen Shuai; Deyin Zhao; Yonghao Liu; Corey Stambaugh; John Lawall; Weidong Zhou (IEEE Photonics Journal, 2017)
We demonstrate here a surface-normal ultracompact Fano resonance electro-optic spatial light modulator employing a stacked photonic crystal membrane capacitor-like structure. Vertically coupled optical resonance near 1.5 μm was observed, and both blue and red spectral shifts were achieved by means of appropriate electrical bias. A 200-MHz modulation bandwidth was obtained on a device with an 80 μm × 80 μm mesa area, while bandwidths in the gigahertz range are expected by shrinking the mesa lateral size down to 20 μm × 20 μm. We fabricated 6 × 6 arrays with different mesa sizes on a silicon-on-insulator platform, illustrating the potential of these devices in vertically integrated photonic technologies and for high-speed spatial light modulations.